DINAMIKA POPULASI PSEUDOMONAS PUTIDA PF-20 DAN RALSTONIA SOLANACEARUM PADA RIZOSFER TANAMAN TOMAT - , RATNA WAHYUNINGTYAS, Prof. Dr. Ir. Triwidodo Arwiyanto, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Tomato is an agricultural commodity containing nutrients for human health. Problem faced in tomato production is bacterial wilt caused by Ralstonia solanacearum. Some methods have been used for manage it, one of them is using biocontrol agent Pseudomonas putida Pf-20. The research aims to know population dynamic of P. putida Pf-20 and R. solanacearum in the tomato rizosphere. The P. putida Pf-20 isolate used was a collection of Laboratory of Plant Bacteriology, Departement of Plant Protection, Faculty of Agriculture, Universitas Gadjah Mada, Yogyakarta. P. putida Pf-20Rif population in treatment without R. solanacearum declined from time to time. In R. solanacearum inoculated treatment, P. putida Pf-20Rif population fluctuated. In the first observation the population was lower than those in treatment without R. solanacearum. The population declined on the second observation and then increased in third and fourth observation closer to P. putida Pf-20Rif population in treatment without R. solanacearum.